KONSEP FILSAFAT PENDIDIKAN MUHAMMADIYAH - Khosiah, Nur; Nurhakim, Moh; Amin, Syaiful (LPPM STAI Muhammadiyah Probolinggo, 2024)
Philosophy is the mother of science, all humans are good at philosophy because they are given the advantage of thinking by Allah SWT. The aim of this research is to find out what the concept of Muhammadiyah educational philosophy is. This research uses a descriptive qualitative approach with library research methods. Which results in the conclusion that Muhammadiyah is an educational institution that has a non-political nature. The characteristic of Muhammadiyah education is the existence of Al-Islam and Muhammadiyah education at the elementary school level to the tertiary level. Muhammadiyah, with the motto